ANALISIS NUMERIK KONVEKSI ALAMI DALAM ANNULUS KONSENTRIK DEN GAN METODE ARTIFICIAL COMPRESSIBILITY - Pranowo, Pranowo (Mesin, 2000)
This paper discusses numerical solution of natural convection in concentric annulus. Artiï¬cial Compressibility Method has been used to solve two dimensional Navier Stokes equations. And to strengthen the relationship between pressure and velocities, pressure was placed on the cell center, whereas the velocities and temperature were placed on cell vertex. Navier Stokes Equations were divided into discrete forms by ï¬nite volume method, so that ï¬ow conservation could be kept balance. The computation results show no signiï¬cant difference with the other results solved using other computation method.